Chemigation Equipment and Techniques for Citrus - Brian Boman; Sanjay Shukla; Dorota Haman (EDIS)
Chemical application through irrigation systems is called chemigation. Chemicals used can include a variety, such as fertilizer, insecticides, fumigants, and soil amendments. Chemicals can be any substance which is intended for agricultural purpose. Some of these chemicals are termed as toxic chemicals and include pesticides whose labels bear the signal words "Danger" and/or "Poison." This document is Circular 1403, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2004.